USING SEMANTIC MAPPING TO IMPROVE 9th GRADE STUDENTS’ VOCABULARY MASTERY IN MTS AL MUBAROKAH BATUJAJAR IN THE ACADEMIC YEAR OF 2016/2017 - Sopian, Ade (IKIP Siliwangi, 2018)
The objectives of this research entitled “Using Semantic Mapping to improve 9th-gradestudents vocabulary mastery in MTs Al-Mubarokah Batujajar in the academic 2016/2017”. Concerning to the problem stated above the purpose of this study is to find out whether the use of semantic mapping. In this research was a quantitative method. The writer will take one class, as experimental. The instrument is pre-test and post-test which is given to both experiment and control class. The population is 60 9th grade students of MTs Al-Mubarokah Batujajar and the sample is 30 students of 9th as experiment class and 30 students of 9th as control class. The data analysis is computed by IBM SPSS Ver.16 using Mann Whitney U test with 0,05 level of significance. The test result showed that the score is 0,036 which less than 0,05 (0,036 < 0,05). Based on the data, it can be concluded that null hypothesis is rejected and the alternative hypothesis is accepted. In other words, there is the significant difference between students’ achievement in experiment and control class which indicates that Semantic Mapping technique can improve students’ Vocabulary Mastery.